2021
DOI: 10.1038/s41419-021-03954-8
|View full text |Cite
|
Sign up to set email alerts
|

Growth differentiation factor 11 attenuates cardiac ischemia reperfusion injury via enhancing mitochondrial biogenesis and telomerase activity

Abstract: It has been reported that growth differentiation factor 11 (GDF11) protects against myocardial ischemia/reperfusion (IR) injury, but the underlying mechanisms have not been fully clarified. Considering that GDF11 plays a role in the aging/rejuvenation process and that aging is associated with telomere shortening and cardiac dysfunction, we hypothesized that GDF11 might protect against IR injury by activating telomerase. Human plasma GDF11 levels were significantly lower in acute coronary syndrome patients than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 60 publications
2
6
0
Order By: Relevance
“…Next, we sought to study myocardial expression levels of both Gdf11 and Mstn in mice undergoing myocardial I/R injury and their respective controls. In line with previous reports in 8–10-week-old mice, 59 , 60 a marked decline in Gdf11 but an increase in Mstn expression was observed upon I/R ( Figure 1 B ). Of note, Magga et al 59 have shown that these changes are accentuated early after I/R and are more prominent in the infarcted rather than the peri-infarcted area, suggesting that changes in endogenous Gdf11 expression levels are predominantly induced by the ischaemic insult, and as such interfering with Gdf11 signalling may have therapeutic effects.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Next, we sought to study myocardial expression levels of both Gdf11 and Mstn in mice undergoing myocardial I/R injury and their respective controls. In line with previous reports in 8–10-week-old mice, 59 , 60 a marked decline in Gdf11 but an increase in Mstn expression was observed upon I/R ( Figure 1 B ). Of note, Magga et al 59 have shown that these changes are accentuated early after I/R and are more prominent in the infarcted rather than the peri-infarcted area, suggesting that changes in endogenous Gdf11 expression levels are predominantly induced by the ischaemic insult, and as such interfering with Gdf11 signalling may have therapeutic effects.…”
Section: Resultssupporting
confidence: 93%
“…Mstn and Gdf11 share many functional properties for muscle mass control in mice, 75 but the contrasting myocardial expression pattern during ageing and upon I/R injury ( Figure 1 B ) 59 , 60 coupled with marked differences in their predictive utility for final infarct size in human patients ( Figure 5 C ) strongly suggests that GDF11 and MSTN play distinct roles during I/R injury. In fact, both aptamer- and antibody-based detection methods commonly employed in the past were found to be non-specific for GDF11 (and thus to cross-react with MSTN): indeed, in contrast to the initial paradigm, 27 , 28 various studies have reported variable or no significant age-related change in GDF11 protein levels in humans.…”
Section: Discussionmentioning
confidence: 99%
“…BMP-11 overexpression with an adenovirus was reported to alleviate cardiac ischemia-reperfusion injury by enhancing mitochondrial biogenesis and telomerase activity in rats (Chen et al, 2021). These researchers also found that BMP-11 depletion resulted in the opposite effect in mice (Chen et al, 2021).…”
Section: The Bmp Family and Myocardial Remodelingmentioning
confidence: 93%
“…BMP-11 overexpression with an adenovirus was reported to alleviate cardiac ischemia-reperfusion injury by enhancing mitochondrial biogenesis and telomerase activity in rats (Chen et al, 2021). These researchers also found that BMP-11 depletion resulted in the opposite effect in mice (Chen et al, 2021). Furthermore, BMP-11 overexpression reduced cardiomyocyte apoptosis and improved cardiac function, thus enhancing myocardial regeneration after ischemia-reperfusion injury in aging mice (Du et al, 2017).…”
Section: The Bmp Family and Myocardial Remodelingmentioning
confidence: 96%
“…By the same token, overexpression of telomerase can confer cardioprotection in mice hearts (60). Furthermore, overexpression of growth differentiation factor 11 (GDF11) in mice subjected to in vivo I/R injury showed a reduced infarct size, activation of telomerase, longer telomeres and increased mitochondrial biogenesis (61). In a clinical context, Gupta et al have published a pilot study that proposes telomere length as a screening tool for patients with acute myocardial infarction (62).…”
Section: Telomerase Activity In Aging and Cardioprotectionmentioning
confidence: 99%